2009
DOI: 10.1111/j.1475-1313.2009.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effect of facial topographies upon the visual field of humans and primates

Abstract: The model provides information on anatomical constraints for monocular and binocular visual field extensions including projection of the ventral field on a virtual floor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As can be seen in Table 1, the most commonly reported manufacturer used for fully noninvasive primate testing is Tobii (Tobii Technology, Sweden). Given that (Tobii) eye trackers have been developed for use with human participants, and primates' eyes and faces differ from humans in terms of size and morphology (e.g., Glittenberg et al, 2009;Kobayashi & Kohshima, 2001) as well as interpupil distance, users have reported varying success across the different models for use with primates (e.g., Kano, Call, & Tomonaga, 2012, reported that the eye tracker they used [Tobii X120] was unable to track both eyes of one adult male gorilla due to the wide distance between his eyes). In spite of this, Kano and Tomonaga (2009) reported that for humans and chimpanzees tested under comparable protocols (using Tobii X120), "the average error when viewing the screen (the distance between measured and intended gaze points) was less than 0.5°in both species, p 1950."…”
Section: Hardwarementioning
confidence: 99%
“…As can be seen in Table 1, the most commonly reported manufacturer used for fully noninvasive primate testing is Tobii (Tobii Technology, Sweden). Given that (Tobii) eye trackers have been developed for use with human participants, and primates' eyes and faces differ from humans in terms of size and morphology (e.g., Glittenberg et al, 2009;Kobayashi & Kohshima, 2001) as well as interpupil distance, users have reported varying success across the different models for use with primates (e.g., Kano, Call, & Tomonaga, 2012, reported that the eye tracker they used [Tobii X120] was unable to track both eyes of one adult male gorilla due to the wide distance between his eyes). In spite of this, Kano and Tomonaga (2009) reported that for humans and chimpanzees tested under comparable protocols (using Tobii X120), "the average error when viewing the screen (the distance between measured and intended gaze points) was less than 0.5°in both species, p 1950."…”
Section: Hardwarementioning
confidence: 99%
“…16 Virtual reconstructions of human and primate faces in computer modeled perimeters have identified the limiting role of the nasal ridge and other aspects of facial anatomy on the visual field, but again the effect of head turn on these anatomic limitations was not assessed (virtually or otherwise). 17…”
mentioning
confidence: 99%
“…16 Virtual reconstructions of human and primate faces in computer modeled perimeters have identified the limiting role of the nasal ridge and other aspects of facial anatomy on the visual field, but again the effect of head turn on these anatomic limitations was not assessed (virtually or otherwise). 17 This study aims to determine whether the areas of decreased peripheral visual field sensitivity caused by prominent facial anatomy on 60-4 testing can be overcome by turning the head in patients with otherwise normal visual function.…”
mentioning
confidence: 99%